Fatigue Analysis of Mid-Water Buoy (MWB) due to Changes in Pipeline End Manifold (PLEM) Position - Rahmatulloh, Ibrahim; Handayanu; Syahroni, Nur (International Journal of Marine Engineering Innovation and Research, 2025)
This research is a case study of the Mid-Water Buoy (MWB) structure on the subsea hose string SPM #4 after the installation of New PLEM C, or in other words in conditions where the subsea hose string (including MWB) has been connected to New PLEM C. MWB is one of the ancillary components of the subsea hose string, which has the main function as a buoy to keep the entire subsea hose string at a safe distance to the seabed. By replacing the old PLEM-C with the New PLEM-C, the dynamic motion of the subsea hose when connected to the New PLEM-C will also be different compared to the dynamic motion when connected to the old PLEM-C. The objective of this study is to analyze the fatigue life of the MWB structure after the use of New PLEM-C. As the main input for fatigue analysis, cyclic load analysis acting on the MWB structure is carried out based on a deterministic approach through time domain simulation and continued with the calculation of the number of cycles with the rainflow cycle counting method. For local stress analysis in the critical area of the MWB structure, the hotspot stress method is carried out through the Finite Element Method (FEM) which refers to DNV-RP-C203. Furthermore, the fatigue life calculation is carried out by applying the Palmgren-Miner rules and utilizing the S-N Curve. From a series of analyses that have been carried out it was found that the lowest fatigue life value for the MWB structure is occurs at PART B1 (the part of the MWB connected to the Subsea Hose STRING B – Upper) with a value of 145.93 years and with an annual damage ratio of 0.0069 for the Connection between the Vertical Stiffener and the Pipe.